Will IT Technologies and Globalisation Change the Mechanism of Money Creation? - Sławiński, Andrzej (Journal of Public Governance, 2020)
Objectives: The article addresses the question about whether IT technologies and the ongoing globalisation are likely to impact the money creation mechanism.Research Design & Methods: For this purpose, the article reviews the experiences of free banking, the endeavours to promote the bitcoin as a new currency, the discussions on digital currencies issued by central banks, the experiences with Eurodollar market, and the emergence of imbalances in the TARGET2 (the Eurozone payment system).Findings: The analysis leads to two general findings. The first one is that cryptocurrencies are unlikely to replace the existing monetary system. The second one is that the increasing globalisation creates the need for the most important central banks to expand their role as international lenders of last resort.Implication / Recommendations: One implication of the main findings of the paper is that cryptocurrencies will have to go through a long evolution before they might have a chance to become an integral part of the monetary systems instead of being purely speculative assets. The other implication is that the experiences with the TARGET2 system revealed the ECB’s large potential to prevent sudden halts in international trade.Contribution / Value Added: The article’s added value with regard to the existing literature is highlighting that the main reason why the deposit money created by commercial banks (making the bulk of money supply today) will not be replaced by cryptocurrencies stems mainly from the fact that the latter cannot be allocated in an economically rational way. The other contribution is underscoring that the TARGET2 imbalances reflected the positive role played by the ECB in alleviating the consequences of the global banking crisis of 2007-2009 and the Eurozone debt crisis of 2010-2012.